EFEKTIVITAS PELATIHAN KETERAMPILAN LAS DI PANTI SOSIAL BINA REMAJA KECAMATAN RUMBAI KOTA PEKANBARU - Doni Lagoda Manurung; Sumardi Sumardi; Jasfar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research is motivated by problems that occur in the field, namely: welding skills trainees are often absent and playing around during welding skills training in progress, participants must take turns using welding equipment in welding skills training because there is still a minimum amount provided, work safety is not considered this seen from the lack of work safety equipment used during practice, the ability of the participant’s welding skills is uneven, this can be seen from the quality of the goods done by each participants. The purpose of this study was to determine the Effectiveness of Welding Skills Training at PSBR, Rumbai District, Pekanbaru. The purpose of welding skills training in PSBR against teenagers drop out of school and are displaced to be able to live independently and avoid various social problems for themselves and their environment and can develop their potential owned so that it can carry out its social functions. This research is descriptive qualitative approach. This research method uses descriptive research with qualitative approach. The techniques of collecting data used are observation, documentation, and interviews. Data analysis techniques aim to simplify the processed data so that it is easy to read and understood. The data analysis technique is through three stages, namely data reduction, data presentation, and data verification. The results of the data analysis carried out can be seen that the welding skills training in Bina Remaja Social Institution in Rumbai District, Pekanbaru is less effective, the participants are training in welding skills are still not able to be independent, the facilities and infrastructure inside welding skills training is incomplete, training participants in welding skills are not on time at the training venue. The conclusions on welding skills training at the Adolescent Bina Social Institution Rumbai District Pekanbaru is implemented and runs smoothly but has not been effective based on measurement of effectiveness. Keywords: Effectiveness, Weld Skill Training